Lapses 1 : Pavilion of Turkey during 53rd International Art Exhibition, La Biennale di Venezia - Senova, Basak; Odelli, Nusin; Gurlek, Nazli; Biennale di Venezia Venice 2009 (Istanbul : [s.n.], 2009)
Cennetoglu, Banu ; Ögüt, Ahmet
Turkish Pavilion, Venice, Giardini, June 6 - November 22, 2009
kunstcatalogus